Tc9 cells, a new subset of CD8+ T cells, support Th2‐mediated airway inflammation. Issue 3 (31st January 2013) - Visekruna, Alexander; Ritter, Josephine; Scholz, Tatjana; Campos, Lucia; Guralnik, Anna; Poncette, Lucia; Raifer, Hartmann; Hagner, Stefanie; Garn, Holger; Staudt, Valerie; Bopp, Tobias; Reuter, Sebastian; et al.
<x xml:space="preserve">Abstract</x> Similar to T‐helper (Th) cells, CD8+ T cells also differentiate into distinct subpopulations. However, the existence of IL‐9‐producing CD8+ T (Tc9) cells has not been elucidated so far. We show that murine CD8+ T cells activated in the presence of IL‐4 plus TGF‐β develop into transient IL‐9 producers characterized by specific IFN‐γ and IL‐10 expression patterns as well as by low cytotoxic function along with diminished expression of the CTL‐associated transcription factors T‐bet and Eomesodermin. Similarly to the CD4+ counterpart, Tc9 cells required for their differentiation STAT6 and IRF4. Tc9 cells deficient for these master regulators displayed increased levels of Foxp3 that in turn suppressed IL‐9 production. In an allergic airway disease model, Tc9 cells promoted the onset of airway inflammation, mediated by subpathogenic numbers of Th2 cells. This support was specific for Tc9 cells because CTLs failed to exert this function. We detected increased Tc9 frequency in the periphery in mice and humans with atopic dermatitis, a Th2‐associated skin disease that often precedes asthma. Thus, our data point to the existence of Tc9 cells and to their supportive function in Th2‐dependent airway inflammation, suggesting that these cells might be a therapeutic target in allergic disorders.